PENGARUH KOMUNIKASI DALAM REFERENCE GROUP TERHADAP TINDAKAN BOIKOT PRODUK TERAFILIASI ISRAEL YANG DIMEDIASI SIKAP POLITIK PADA MAHASISWA KOTA SEMARANG - Cytania Noarya Ailani; Yanuar Luqman (Interaksi Online, 2026)
This research is motivated by the rise of economic boycott movements against Israel affiliated commercial products as a form of humanitarian solidarity regarding the geopolitical crisis in Palestine. Information about this movement is actively circulating within university students' reference groups, yet an attitude behavior gap remains visible in their daily consumption behavior. The purpose of this study was to determine the effect of reference group communication on the boycott action of Israel-affiliated products, both directly and indirectly through the mediation of political attitudes among university students in Semarang City. The theories used in this study are Reference Group Theory and the Theory of Reasoned Action (TRA). Using a quantitative approach, this study involved 100 respondents, all of whom were university students in Semarang City exposed to the product boycott movement issues. Data collection used a questionnaire survey. The data were then analyzed through sequential inferential analysis using multi-stage linear regression (causal steps) to understand the influence of the independent variable on the dependent variable through the mediator variable. The results of this study indicate that communication within the reference group has a positive and significant influence on students' political attitudes, and political attitudes are proven to have a significant positive effect on driving actual boycott actions. Furthermore, step-by-step testing proves that political attitude acts as a significant mediating variable that bridges the influence of reference group communication interaction toward the manifestation of actual boycott behavior in daily life. Discussion channels and information exposure from close peer circles can reduce the behavior gap when successfully internalized into strong moral beliefs and evaluative judgments within individual students. In conclusion, the results of this study demonstrate that the formation of ethical consumption actions (political consumerism) among university students does not merely depend on the intensity of information circulation within their social environments, but is heavily determined by the stability of individual political attitudes built through that communication. Future social movement strategies need to focus more on strengthening value education and providing valid literature data within group communication channels, ensuring that collective awareness can consistently transform into sustainable actual actions.